2005
DOI: 10.1111/j.1365-2109.2005.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Captive breeding of climbing perch Anabas testudineus (Bloch, 1792) with Wova-FH for conservation and aquaculture

Abstract: Induced breeding of climbing perch, Anabas testudineus was conducted by synthetic hormone Wova-FH in the intensity level of 0.1, 0.2 and 0.3 mL kg À1 of body weight respectively. The brooders were injected one time and left to spawn in the spawning hapa in the sex ratio between male and female as 2:1. It was found that at all the intensity level hormoneWova-FH could enhance the ¢shes to breed and lay eggs whereas no breeding was observed in control set. The spawning time, quantity of the brooder spawn, fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 4 publications
2
20
2
3
Order By: Relevance
“…The egg diameter of 0.86-0.92 mm observed in the present study was greater than that reported by Sarkar et al (2005) (0.60-0.84 mm). In addition, whereas Sarkar et al (2005) reported larval length larger than 7 mm on day-5 and 22.4 mm a month after hatching, the BL (mean ± SD) observed in this study on days-5 and 30 were 4.8 ± 0.2 mm and 16.9 ± 2.3 mm, respectively (Fig. 1), despite similar water temperatures in both cases [average 28.4°C (in the present study) vs. 28.5°C].…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The egg diameter of 0.86-0.92 mm observed in the present study was greater than that reported by Sarkar et al (2005) (0.60-0.84 mm). In addition, whereas Sarkar et al (2005) reported larval length larger than 7 mm on day-5 and 22.4 mm a month after hatching, the BL (mean ± SD) observed in this study on days-5 and 30 were 4.8 ± 0.2 mm and 16.9 ± 2.3 mm, respectively (Fig. 1), despite similar water temperatures in both cases [average 28.4°C (in the present study) vs. 28.5°C].…”
Section: Discussioncontrasting
confidence: 80%
“…According to Sarkar et al (2005), Anabas testudineus collected from Punarbhaba River, West Bengal, India, spawned on average more than 100,000 eggs per female (average weight 67 g), very much more than the quantity obtained either in this study (ca. 14,000 eggs) from one female weighing 50 g or in another artificial breeding trial (ca.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Anabas testudineus has been considered a possible new target fish species for commercial aquaculture since around the year 2000 (Sarkar et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Anabas testudineus is an important commercial fish in Southeast Asia and usually sold alive at a high price in local markets. Anabas testudineus is now threatened by environmental changes, such as land development and, increasing demand for fish, resulting from a growing human population that relies of fish as its primary animal protein source (Baird et al 2003), Anabas testudineus has been considered a possible new target fish species for commercial aquaculture since around the year 2000 (Sarkar et al 2005). Although aquaculture will help to fulfil the increasing demand for food, it may cause genetic disturbance in natural populations.…”
Section: Introductionmentioning
confidence: 99%